The construction of Heidegger’s existential space. Active void in Oteiza and receptive space in Judd - Llamazares Blanco, Pablo; Ramos Jular, Jorge; Zaparaín Hernández, Fernando (Estoa. Journal of the Faculty of Architecture and Urbanism, 2020)
The sculptural works developed by Jorge Oteiza and Donald Judd since the mid-twentieth century, deepen in the influence between artistic disciplines, which remove the spatial limits between sculpture and architecture. The space gets a great role in this sense, since from the reading of the void proposed by Martin Heidegger through his lecture entitled The art and space, the sculpture put together the artistic object and the viewer in a phenomenological experience, which reminds to the most basic spatial condition of the architectural fact. Through the analysis of the active void of Oteiza and the receptive space of Judd, the article delves into the spatial theories proposed by both artists, which are influenced by the existentialist philosophy of Heidegger and which reach their maximum expression by different paths in their multiple collaborations with architecture. A spatiality of sculptural practice, which stablishes a great chapter in the interdisciplinary creative processes between sculpture and architecture.